TUBEROUS SCLEROSIS COMPLEX- RADIOLOGICAL FEATURES IN DIFFERENT BODY SYSTEMS - Apostoloska, Veronika; Jovanovska, Elizabeta Stojovska; Dimitrovska, Maja Jakimovska; Kocev, Smiljana Bundovska; Crcevska, Sofija; Stavreski, Nacko (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Tuberous sclerosis (TS) is a rare genetic disorder of autosomal - dominant inheritance. Tuberous sclerosis complex is characterized by the development of benign tumors affecting different body systems who results in hamartomas involving many organs, like the brain, heart, kidneys, skin, lungs and liver. The management of these patients is often multidisciplinary, involving specialists from various fields. TSC presents at any age as a wide range of clinical and phenotypic manifestations with varying severity. The most common manifestations are facial angiofibroma, seizures, cortical tubers, cardiac rhabdomyoma, renal cysts and tumor of the kidneys. We present four patients with characteristic clinical and radiological features of multilocular tuberous sclerosis. Keywords: Tuberous sclerosis complex (TSC), tuberous sclerosis (TS), cortical tubers, angiofibromas, renal angiomyolipomas (AML).